2018
DOI: 10.21470/1678-9741-2017-0152
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Surgical Resection of Primary Non-Myxoma Cardiac Tumors

Abstract: ObjectivePrimary cardiac tumors are rare lesions with different histological type. We reviewed our 17 years of experience in the surgical treatment and clinical results of primary non-myxoma cardiac tumors.MethodsBetween July 2000 and February 2017, 21 patients with primary cardiac tumor were surgically treated in our institution. The tumors were categorized as benign non-myxomas and malignants. Data including the demographic characteristics, details of the tumor histology and grading, cardiac medical and surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…We found that the tumor stage was an independent prognostic factor for both OS and CSS in PMCTs, which is consistent with the previous studies that tumor stage had a prognostic association with OS in PMCTs. We also identified cancer‐directed surgery as an independent prognostic factor for OS and CSS in PMCTs, which concurred with the Mayo Clinic experience that surgical excision of primary cardiac tumors was associated with better survival and a complete resection should be performed if possible …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found that the tumor stage was an independent prognostic factor for both OS and CSS in PMCTs, which is consistent with the previous studies that tumor stage had a prognostic association with OS in PMCTs. We also identified cancer‐directed surgery as an independent prognostic factor for OS and CSS in PMCTs, which concurred with the Mayo Clinic experience that surgical excision of primary cardiac tumors was associated with better survival and a complete resection should be performed if possible …”
Section: Discussionsupporting
confidence: 85%
“…We also identified cancer-directed surgery as an independent prognostic factor for OS and CSS in PMCTs, which concurred with the Mayo Clinic experience that surgical excision of primary cardiac tumors was associated with better survival 28 and a complete resection should be performed if possible. 9,29 We also identified chemotherapy as an independent prognostic factor for OS and CSS in PMCTs. Previous reports 14,25 believed that chemotherapy was a preferred primary treatment modality for primary cardiac lymphoma patients because of the sensitivity of lymphoma to chemotherapy, and chemotherapy might prolong OS in primary cardiac sarcomas but it was not confirmed.…”
Section: F I G U R Ementioning
confidence: 73%
“…7,8 As 75-80% of the tumors arise in the left atrium, approximately half of the embolic events may affect the central nervous system (CNS). 9 The neurological manifestation of cerebral embolization depends on whether embolic tumor cells remain intraluminal, leading to ischemic stroke, invade the vessel wall, resulting in intracranial aneurysms, or, in rare circumstances, transgress the vessel wall, leading to brain parenchymal seeding. 10 Factors related to the intracranial dissemination of left cardiac myxomas remain unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…Although PMCT patients have a dismal prognosis, our study confirms surgical resection and chemotherapy are associated with a favourable early prognosis. In one study, clinical experience suggested cancer-directed surgical excision was associated with better survival in PMCTs patients (26)(27)(28). Surgery intervention is mostly performed in those at an advanced tumor stage, as without it PMCTs can cause hemodynamics disorder, heart failure, hemorrhagic pericardial effusion, and supra-ventricular arrhythmia in a short time.…”
Section: Discussionmentioning
confidence: 99%